Investigating nutrient intake during use of glucagon-like peptide-1 receptor agonist: a cross-sectional study - Johnson, Brittany; Milstead, Mary; Thomas, Olena; McGlasson, Tyler; Green, Lauren; Kreider, Rachel; Jones, Rachel (Frontiers in Nutrition, 2025)
BackgroundGlucagon-like peptide-1 receptor agonist (GLP-1RA) pharmaceutical interventions have advanced medical treatment for obesity, yet little is known about nutrient intake while using a GLP-1RA. The purpose of this study was to compare nutrient intake while using a GLP-1RA to the Dietary Reference Intakes (DRI).MethodsA cross-sectional study was conducted in a sample of participants who had been using GLP-1RA for at least one month (N = 69). Participants answered online survey questionnaires and completed a 3-day food record. Descriptive statistics (means, standard deviations) were calculated for all participant demographic characteristics and average 3-day nutrient intakes. Average 3-day nutrient intakes were compared to the DRI using 95% confidence intervals (CI). A Bonferroni correction applied accepted significance at p ≤ 0.00156. One-way ANOVA analysis was conducted to compare the self-reported MyPlate servings to recorded servings from the 3-day food record.ResultsCompared to the DRI reference values, participants consumed adequate amounts of B-vitamins, copper, phosphorus, selenium, and zinc. Participants had insufficient intakes of several key nutrients below the DRI, including fiber (14.5 g; CI: 12–17), calcium (863 mg; CI: 756–970), iron (12.1 mg; CI: 11–13), magnesium (266 mg; CI: 236–297), potassium (2,186 mg; CI: 1,969–2,402), choline (305 mg; CI: 268–342), vitamin A (560 mcg RAE; CI: 469–651), vitamin C (51 mg; CI: 41–61), vitamin D (4 mcg; CI: 3–5), vitamin E (9.6 mg; CI: 8–11), and p < 0.00156. Participants overconsumed % calories from fat (39.9%; CI: 38, 42), and saturated fat (26 g; CI: 26, 26), p < 0.00156. Participants did not meet the daily recommended MyPlate servings for fruit, vegetables, grains, or dairy (p < 0.01). Protein intake (% total calories) was within the AMDR, however based on a g/kg/day, protein intake was significantly under daily needs.ConclusionParticipants on a GLP-1RA are not meeting the DRI for several vital nutrients through their diet or higher protein needs during weight loss. Patient-centered nutritional guidance is essential to optimize health outcomes and prevent unintended health consequences. Future large-scale studies are needed to assess the replicability of these findings and provide custom nutritional guidance for those on a GLP-1RA medication.